Using Picture Series in Improving Students’ Writing Skill in Recount Text - Saripah, Wa (PANYONARA: Journal of English Education, 2024)
Abstract: Writing skill is important and beneficial in English language learning. Having good writing skill enables learners in language learning to do communication. Problem in writing is a language barrier to written communication. This action research aims to overcome students’ problem in writing in terms of recount text by applying pictures series. The procedures of classroom action research were used to investigate the process and the subject’s outcomes. There were 33 students of 8th grade (VIII-1) at MTs Negeri 1 Muna who enrolled in the academic year 2022/2023 for the subject of this research which was taken purposively. The researcher uses writing tests and field notes to gather the data. The study was accomplished in two cycles. The successful research is indicated by students’ average scores meeting the minimum target (75). In cycle 1 the students obtained 66.87 on average. Another improvement in cycle 2 appeared, the students reached 81.31 on average. The result from this research indicates that students’ writing improved after picture series was used in the learning process.